Malignant T Cell Activation by a Bacillus Species Isolated from Cutaneous T-Cell Lymphoma Lesions - Carina A. Dehner; William E. Ruff; Teri Greiling; Márcia S. Pereira; Sylvio Redanz; Jennifer McNiff; Michael Girardi; Martin A. Kriegel (Elsevier, 2022)
Cutaneous T-cell lymphoma (CTCL) is a life-debilitating malignancy of lymphocytes homing to the skin. Although CTCL is thought to arise from a combination of genetic, epigenetic, and environmental factors, specific triggers are unclear. The skin is colonized by a unique microbiota and is heavily influenced by its interactions. We hypothesized that adaptive immune responses to skin commensals lead to clonal T-cell proliferation and transformation in the appropriate genetic background. We therefore collected lesional and nonlesional skin microbiota from patients with CTCL to study T cell interactions using skin T cell explants and peripheral, skin-homing CD4+ T cells. By various methods, we identified Bacillus safensis in CTCL lesions, a rare human commensal in healthy skin, and showed that it can induce malignant T cell activation and cytokine secretion. Taken together, our data suggest microbial triggers in the skin microbiota of patients with CTCL as potential instigators of tumorigenesis.